2020
DOI: 10.1007/s00477-020-01926-6
|View full text |Cite
|
Sign up to set email alerts
|

A revised range of variability approach considering the morphological alteration of hydrological indicators

Abstract: Li, and Youwei Qin. The methodology was proposed by Xin Zheng, Tong Cui and Tao Yang.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…The test for mutation points is first observed by the Mann-Kendall mutation test to discover whether the two curves UF, UB intersect at a given confidence level α, and then the mean difference t-test is used to further corroborate and discover whether the mutation year meets the mutability test need. For detailed steps refer to the literature [16].…”
Section: Analysis Of the Average Annual Water Temperature Variation Trend And The Mutation Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The test for mutation points is first observed by the Mann-Kendall mutation test to discover whether the two curves UF, UB intersect at a given confidence level α, and then the mean difference t-test is used to further corroborate and discover whether the mutation year meets the mutability test need. For detailed steps refer to the literature [16].…”
Section: Analysis Of the Average Annual Water Temperature Variation Trend And The Mutation Testmentioning
confidence: 99%
“…Range of Variability Approach and indicator of Hydrologic Alteration was selected to establish the evaluation of ecological hydrological index and quantify the variation degree of river hydrological regime [16,17], calculated by the following equation:…”
Section: Analysis Of the Degree Of Water Temperature Variationmentioning
confidence: 99%
“…All of the above alteration assessment methods do not consider the morphological characteristics of IHAs which are crucial from the perspective of hydro‐ecology. Zheng et al (2021) connected the magnitude and location (i.e., time order) of the samples through the Hasse matrix, and proposed the Revised Range of Variability Approach (RRVA), which indicates the conjoint changes in temporal sequence and indicator frequency to assess hydrologic regime comprehensively. The RRVA method focuses on the morphology of IHAs in time order, that is, how IHAs vary with time series.…”
Section: Introductionmentioning
confidence: 99%
“…Peng, et al 11 showed that the reduction in peak flows caused by the dams would result in the failure of downstream fish to spawn. Given this challenge, quantitative assessment of changes in characteristic hydrologic parameters 16 and analysis of ecological flows required by the fish spawning process 2 , 11 , 17 are essential for river habitat restoration.…”
Section: Introductionmentioning
confidence: 99%
“…The final step is to assess the variability of hydrologic indicators. Previous studies have shown that the range of variability approach (RVA) in combination with IHAs can successfully and powerfully reveal flow regime changes 16 . However, they ignored the frequency of the natural flow, which was already altered 29 .…”
Section: Introductionmentioning
confidence: 99%